PERLINDUNGAN HUKUM KONSUMEN SEBAGAI PEMEGANG LEASING YANG WANPRESTASI DALAM PERJANJIAN LEASING (Studi Pada PT. Federal International Finance Group) - Tangges Dines; Kusbianto Kusbianto; Ayu Trisna Dewi (Law Jurnal, 2022)
ABSTRACTLeasing is often used as a god of help or a god of savior for most Indonesian people. However, at this time the existence of leasing that violates the law on the forced withdrawal of goods that are the object of leasing is very disturbing to consumers.The problems in this study are the position of the leasing consumer in the event of a default in the leasing agreement, the dispute resolution process due to default against the leasing company at PT FIF GROUP. and implementation of confiscation of goods (Objek Leasing) at PT FIF GROUP. This research method uses empirical legal research and descriptive analytical research.If the customer has exceeded the promised time limit, the customer will get (bad RO) and the customer will also be blacklisted from the company and will not be able to apply for credit withdrawal at any leasing company or dealer he wants to take credit for. If the customer makes payments smoothly and there are no obstacles, the customer will have a good position. Settlement of disputes in leasing contracts can be done in two ways, namely through court and out of court. Implementation of the trial based on court decisions or the decision of the Constitutional Court no. 18/PUU-XVII-2019 there has been no confiscation by PT. FIF. Determination of court confiscation to withdraw the object of leasing as determined by the Constitutional Court (MK). It is suggested that PT FEDERAL INTERNATIONAL FINANCE should use more government regulations, namely using court decisions or decisions of the Constitutional Court to confiscate or take goods (leasing objects).Keywords: Leasing, Achievement Wan, Confiscation of Goods